1979
DOI: 10.1159/000250737
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo Associated with BCG-Methanol Extraction Residue in Malignant Melanoma

Abstract: A pronounced vitiliginous reaction developed at the sites of MER/BCG injections given as an adjuvant immunotherapy to a patient with malignant melanoma. To our knowledge, this is the third report on patients exhibiting vitiligo apparently induced by immunotherapy and the first in association with MER. This association may be a sign for an antimelanocytic effect and may offer a further confirmation for the autoimmune nature of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The worldwide prevalence of vitiligo has been estimated as 0.5% 24 . The association between vitiligo and MM has been described by several investigators 1,2,8–10,25–46 . The relative rate of this association is still unknown; previous reports have given variable results ranging from 1.4% to 20% 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide prevalence of vitiligo has been estimated as 0.5% 24 . The association between vitiligo and MM has been described by several investigators 1,2,8–10,25–46 . The relative rate of this association is still unknown; previous reports have given variable results ranging from 1.4% to 20% 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al [24] reported a pronounced vitiliginous reaction that developed at the sites of BCG methanol extraction residue injections given as an adjuvant immunotherapy to a patient with malignant melanoma. It may be a sign for an antimelanocytic effect and a further confi rmation for the autoimmune nature of vitiligo.…”
Section: Medications Used For the Treatment Of Melanomamentioning
confidence: 99%